Sexual violence knowledge sharing with Mandar Peduli Community in Tinambung, Majene District, West Sulawesi - Irwan, Muhammad; Rahman, Sari Rahayu; Risnah (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2025)
Sexual violence is a crime that is in the global public spotlight, with adolescents as vulnerable victims of this crime. In Indonesia, sexual violence against adolescents is the highest case among other cases of violence. Lack of knowledge about sexual violence is one of the causes of high cases of sexual violence in adolescents in Indonesia. Therefore, debriefing on sexual violence needs to be done to minimize sexual violence in adolescents. By implementing sharing-knowledge of sexual violence in adolescents, this community service activity aims to share knowledge and minimize sexual violence in adolescents, especially in the Tinambung neighborhood, Majene District, West Sulawesi. The target of this activity is young people in the Tinambung neighborhood who are involved in Mandar Peduli. The method of lecturing and watching movies is the right choice in implementing community service activities. The results of this service activity are expected to increase understanding and awareness of the general public, especially members of the Mandar Peduli community of sexual violence. In addition, there is an agreement in the minutes of the event which is a concrete step that can be taken through Mandar Peduli in the prevention and handling of sexual violence in adolescents, which can mainly be found in various environments in the community through the guidance of the West Sulawesi University sexual violence prevention and handling unit, this is in accordance with the hope that it can make a positive contribution in preventing and controlling sexual violence in the Tinambung Region, West Sulawesi